2007
DOI: 10.1002/mus.20771
|View full text |Cite
|
Sign up to set email alerts
|

Myelinated nerve endings in human skin

Abstract: We used immunohistochemical techniques and confocal microscopy to study the morphometry of myelinated nerve endings in glabrous and hairy skin. A total of 30 healthy volunteers took part in this study designed to assess the possibility of obtaining reliable information on myelinated fibers using samples of hairy skin and to determine whether differences exist between myelinated terminations from different sites. We obtained consistent information on cutaneous myelinated terminations using hairy as well as glab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
126
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 29 publications
(38 reference statements)
3
126
1
Order By: Relevance
“…24 However, some of our findings (warm threshold abnormalities and ENF loss) also suggest an involvement of C fibers in CMT1A, although we cannot have morphologic evidence, since it is not possible to distinguish between C and A-d fibers, whose cutaneous terminal branches are both unmyelinated. 25,26 The involvement of small fibers in conditions affecting mainly large fibers has been previously reported, [27][28][29] implying that congenital or acquired mechanisms underlying the degeneration of large fibers may also affect small fibers. In CMT1A, abnormalities of the interaction between axon and Schwann cells may play a causative role in the distal degeneration of unmyelinated fibers, since PMP22 is also present in the plasma membrane of nonmyelinating Schwann cells.…”
Section: Statistical Analysis We Used Student T Test For Unpaired Datamentioning
confidence: 91%
“…24 However, some of our findings (warm threshold abnormalities and ENF loss) also suggest an involvement of C fibers in CMT1A, although we cannot have morphologic evidence, since it is not possible to distinguish between C and A-d fibers, whose cutaneous terminal branches are both unmyelinated. 25,26 The involvement of small fibers in conditions affecting mainly large fibers has been previously reported, [27][28][29] implying that congenital or acquired mechanisms underlying the degeneration of large fibers may also affect small fibers. In CMT1A, abnormalities of the interaction between axon and Schwann cells may play a causative role in the distal degeneration of unmyelinated fibers, since PMP22 is also present in the plasma membrane of nonmyelinating Schwann cells.…”
Section: Statistical Analysis We Used Student T Test For Unpaired Datamentioning
confidence: 91%
“…Skin biopsies increasingly offer a minimally invasive approach to overcome this problem. Beginning with studies of glabrous 3 and hairy skin, 4 these biopsies have already provided pathogenic information in sensory nerves from patients with CMT1A, such as reduced Meissner corpuscles (MC) density, shortened internodal length, and abnormal paranodaljuxtaparanodal architecture. 5,6 In the present study, we extend these observations in a larger series of patients.…”
mentioning
confidence: 99%
“…Nodal gap was measured as the length of the fiber not marked by MBP ( figure 1, B.a and B.b) and included nodal and part of paranodal regions. 3,4 The measurement of internodal length was performed only when 2 consecutive nodes were identified by tracing the internode on the Z-stack of confocal images (figure 1B.c). Four caliber measurements for each internode (figure 1B.d) were obtained and a mean value was reported.…”
mentioning
confidence: 99%
“…In one study, analysis of the density of parts of the subepidermal nerve plexus with immunofluorescence -when associated with the quantification of IENF density -improved the sensitivity of skin biopsy for diagnosis of SFN 133 . In another study, internode length and internodal gap length of myelinated dermal nerve fibres were quantified and combined with the findings of nerve biopsy, and suggested that the fibres are thin endings of large myelinated Aβ fibres 134 . The same group used this approach to investigate patients with CMT, and demonstrated similar internodal shortening associated with different causal mutations, and a wider nodal gap in the CMT type 1A, providing insight into their role in determining changes of conduction velocity 135,136 .…”
Section: Stromamentioning
confidence: 99%